Construction of probabilistic solutions of the Boltzmann equation - Virchenko, Yu.P.; Karabutova, T.V. (Вопросы атомной науки и техники, 2007)
The proving method of the Cauchy problem solvability of the Boltzmann kinetic equation with spatially uniform initial data in the case of particle scattering cross-section finiteness is proposed. It is based on the construction of the auxiliary vector-valued random process such that the particle velocity distribution function satisfying the Boltzmann equation is the first order marginal probability distribution of this random process.